(E)-3-[(3-Ethoxy-2-hydroxybenzylidene)amino]benzoic acid - Hadi Kargar; Zahra Sharafi; Reza Kia; Muhammad Nawaz Tahir (Acta Crystallographica Section E, 2012)
In the title compound, C16H15NO4, a potential bidentate N,O-donor Schiff base ligand, the benzene rings are inclined to one another by 4.24 (12)°. The molecule has an E conformation about the C=N bond. An intramolecular O—H...N hydrogen bond makes an S(6) ring motif. In the crystal, pairs of O—H...O hydrogen bonds link the molecules, forming inversion dimers with R22(8) ring motifs. These dimers are further connected by C—H...O interactions, forming a sheet in (104). There is also a C—H...π interaction present involving neighbouring molecules.